1983
DOI: 10.1136/hrt.49.5.416
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of smoking after myocardial infarction. Effects on mortality after 10 years.

Abstract: SUMMARY Ten annual cohorts of men suffering from their first myocardial infarction have been followed up to a maximum period of 10.5 years. One thousand and twenty-three male patients of 1306 were smokers. Three months after the infarction 55% had stopped smoking and 45% continued smoking. These two groups were then compared and followed with regard to non-fatal reinfarctions and deaths.Preinfarction characteristics were shown to be similar for the two groups. The prognostic comparability of the two groups was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
3
5

Year Published

1987
1987
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 11 publications
(2 reference statements)
10
70
3
5
Order By: Relevance
“…In fact, the cessation of smoking after AMI has been shown in Western countries to have a beneficial effect on the recurrent adverse events. [5][6][7][8][9][10][11] A recent meta-analysis showed that quitting smoking is associated with reduced risk of total mortality and the pooled crude relative risk was 0.64 (95%CI: 0.58-0.71). 12 In Japan, it has been reported that smoking cessation is associated with reduced second cardiac events (ie, cardiac death and nonfatal MI) in 90 male patients with a history of MI, 27 but that study had the limitations of small sample size, male subjects only and a combined endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the cessation of smoking after AMI has been shown in Western countries to have a beneficial effect on the recurrent adverse events. [5][6][7][8][9][10][11] A recent meta-analysis showed that quitting smoking is associated with reduced risk of total mortality and the pooled crude relative risk was 0.64 (95%CI: 0.58-0.71). 12 In Japan, it has been reported that smoking cessation is associated with reduced second cardiac events (ie, cardiac death and nonfatal MI) in 90 male patients with a history of MI, 27 but that study had the limitations of small sample size, male subjects only and a combined endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…If a CR programme has a high patient uptake and adherence and is effective, it will lead to reductions in risk factors, which in turn should translate to a reduction in cardiac events. 48,[105][106][107][108][109][110][111][112][113][114] At 1 year mortality rates are low (6% in Jolly and colleagues 115 ) and it is unlikely that one would see a reduction in cardiac events. It is also possible that revascularisation rates could be associated with participation in a particular rehabilitation programme.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…Intervention on smoking as objective of primary and secondary prevention of cardiovascular diseases allow for an important reduction of morbimortality, determining a better and greater survival in individuals who stop smoking, of both sexes and in any age range [28][29][30][31][32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%